METHODS OF THE NEURAL NETWORK INFLUENCE ON THE FORMAL TRANSFORMATIVE EXPRESSION OF ARCHITECTURAL STYLES - Kulik, М.; Chupryna, Л.; Ivanenko, Д.; Saienko, Є. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
The potential impact of neural networks on optimizing the design processes in the construction industry cannot be exaggerated. The article analyzes the use of neural networks for creating and processing details and features of architectural and construction styles, particularly functional and hi-tech styles, through the transformative expression by using neural networks. Neural networks (hereafter NNs) have the potential to revolutionize the industry of construction and architecture by providing faster, more efficient, and more accurate processes in generating architectural elements and concept art. The NNs can be used for design optimization, enhancing design proposals, planning and construction by analyzing large volumes of data and determining the most economically viable engineering solutions. The use of neural networks can result in improved productivity in the construction industry. Today, NNs can be applied to analyze various architectural styles using images, generating design iterations based on them. This analysis can help engineers, architects, and designers to better understand the defining characteristics of different styles and apply them in their own projects. Incorporating neural networks in the design optimization process significantly enhances productivity and accuracy. These options can reduce costs of the design and additional design services. The interaction between NNs and information modeling opens new possibilities for improving planning, coordination, and construction management processes. These advantages contribute to error reduction, enhanced accuracy, and decreased project execution risks, which are crucial for successful implementation of construction tasks in the modern world. The continuous advancements in neural networks and their application in construction hold the promise of transforming the industry, fostering innovation, and shaping the future of architectural design and construction practices.